Features of Leading Values and Their Interrelation with Internality in Youth and Maturity - Inna V. Afanasenko (Rossijskij psihologičeskij žurnal., 2016)
The main concern of the paper is to study to the leading values and their interrelation with internality in young and mature persons. The author focused attention on recent psychological research in this eld. The empirical study involved 80 respondents: 40 persons at the age from 19 to 24 (students of various specialties of Rostov-on-Don), 40 persons at the age from 40 to 45 (persons with higher education, representatives of various professions in the city of Rostov-on-Don). This article considers the prevailing ultimate values, features of the structure of individual religiosity and characteristics of internality in the groups of young and mature respondents. The dominance of the value of prosperity was a characteristic feature for the young respondents. The spheres of social life and hobbies were dominant life spheres where the young respondents mainly actualized their values. The spheres of life were not dierentiated in the group of adults, which indicates the individual peculiarity of their distribution in the respondents of this age group. The adult males scored high on measures of faith in the Creator, which is associated with internal locus of control. The overall index of internality in students related to the philosophical perception of religion, development of their religious identity, observance of religious rituals, and recognition of religion as a model of moral norms. The mature persons who had ahobby and aspired to preserve their individuality scored higher on measures of the same characteristic (internality). In this group of respondents the index of internality related to faith in the Creator and in phenomena beyond scientific explanation. Theresults of the study suggest possible applications in psychological consulting onthe problems of value and religious self-determination.